Performance of an Implantable Cardiac Monitor to Detect Atrial Fibrillation: Results of the DETECT AF Study. (7th October 2016) - NÖLKER, GEORG; MAYER, JULIA; BOLDT, LEIF‐HENDRIK; SEIDL, KARLHEINZ; VAN DRIEL, VINCENT; MASSA, THOMAS; KOLLUM, MARC; BRACHMANN, JOHANNES; DENEKE, THOMAS; HINDRICKS, GERHARD; JUNG, WERNER; BRUNNER, KYLE J.; et al.
DETECT AF Study Results: Introduction: Reliable detection and monitoring of atrial fibrillation (AF) is essential for accurate clinical decision making, which can now be done continuously with the introduction of implantable cardiac monitors (ICM) The DETECT AF study evaluated the performance of the Confirm DM2102 ICM (St. Jude Medical, St. Paul, MN, USA) to accurately detect and monitor AF. Methods: Ninety patients previously implanted with the ICM and with either suspected or known paroxysmal AF were enrolled at 12 centers in Germany and The Netherlands. At least 2 weeks after ICM implant, patients wore a Holter monitor for 4 days, while the ICM monitored for AF episodes lasting at least 2 minutes. Holter monitor data was analyzed by a blinded, independent core laboratory and compared to the ICM AF detections. Patient and episode sensitivity (SE), specificity (SP), positive predictive value (PPV), and negative predictive (NPV) were calculated using standard analysis and a generalized estimation equation method where appropriate. Results: A total of 79/90 subjects (61% male, 65.7 ± 9.6 years old) were included in the analysis, totaling 6, 894 hours of Holter monitoring. Using a per patient analysis SE was 100%, PPV was 64.0%, SP was 85.7%, and NPV was 100%. Using a per episode analysis, SE was 94.0% and PPV was 64.0%. With an AF duration analysis, the SE was 83.9%, PPV was 97.3%, SP was 99.4% with an NPV of 98.5%. Conclusion: The SJM Confirm DM2102 can accurately and repeatedly detect paroxysmal AF episodes of at least 2 minutes in length.